MENINGKATKAN TOLERANSI DAN HASIL BELAJAR MELALUI PENERAPAN MODEL DISCOVERY LEARNING PADA CALON GURU SEKOLAH DASAR - Sri Dadi; Panut Setiono (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article is based on the research that aims to (1) improve tolerant behaviour and (2) students’ learning outcomes by applying discovery learning models on the Basic Concepts of Sociology, Anthropology, and History subjects for Elementary School Teacher Education students at the Teacher Training and Education Faculty of Universitas Bengkulu. The method used was Classroom Action Research (CAR). CAR consisted of planning, implementation, observation, and reflection. The results indicated that the implementation of the discovery learning model on the Basic Concepts of Sociology, Anthropology, and History subjects could increase (1) tolerance behaviour and (2) students’ learning outcomes at PGSD FKIP of Universitas Bengkulu. It is recommended for the lecturers who taught courses other than the Basic Concepts of Sociology, Anthropology, and History to apply the discovery learning model because it would provide direct experience to students.